Development of health emergency response capability evaluation framework for primary health institutions in metropolis: based on Delphi method and analytic hierarchy process - Li, Qian; Yu, Hongjie; Cheng, Fan; Kuang, Haidong; Zhang, Xiaoqiong; Shao, Yuqing; Ma, Xiaoxue; Li, Jingyu; Li, Yan; Zhu, Yanhong; Lv, Yipeng (Frontiers in Public Health, 2025)
BackgroundPrimary health institutions, as the “first on-site responders,” play a crucial role in responding to health emergencies. However, there are few studies on the systematic assessment of their emergency response capabilities. We aimed to develop a health emergency response capability evaluation framework for primary health institutions to assess the resuscitation capacity in metropolis.MethodsIn the first stage, we collected preliminary indicators through literature and government documents concerning the primary health evaluation. Afterward, we utilized the Delphi method to consult 15 frontline health emergency response practitioners, health management officials, and research experts. After two rounds of questionnaire consultations, participants scored the importance and feasibility of all indicators. Subsequently, we employed the analytic hierarchy process (AHP) to determine the weights assigned to each indicator and construct the framework of health emergency response capability evaluation for primary health institutions.ResultsWe developed a framework for evaluating the health emergency response capabilities of primary health institutions in metropolis, comprising 3 first-level indicators, 11 s-level indicators, and 37 third-level indicators. In both rounds of consultation, experts provided a unanimous positive consensus, with a 100% agreement rate. The authority coefficient was 0.92 for both rounds, and the p-value of Kendall’s W was statistically significant (<0.001). Furthermore, compared to the first round, the level of coordination among experts improved in the second round. In the process of judging matrices, the consistency ratios (CRs) of indicators at all levels were less than 0.1. For first-level indicators, including “prevention and monitoring,” “resource reserve and system construction,” and “emergency response and summarization,” the respective weight values were 0.286, 0.335, and 0.379, respectively.ConclusionThis study developed a framework for evaluating the health emergency response capabilities of primary health institutions in metropolis. This framework can help improve the evaluation systems for emergency response capacity in primary health institutions in China’s metropolis.